Professor Bauer Has It Backwards - Bancel, Peter (Journal of Scientific Exploration, 2015)
In his essay, Climate Change Science or Climate Change Propaganda?, Henry Bauer informs us that there is no valid scientific support for anthropogenic global warming (AGW), that predictions of future warming are erroneous and that a propaganda campaign is being perpetrated by mainstream science to cover up these embarrassing errors. Worse, the campaign is succeeding as pundits and the media buy into the received dogma and the consequences appear dire. The world risks widespread and unnecessary economic disruption by responding to an illusory problem and "highly informed experts" who challenge the climate change consensus are being hurtfully sneered at as they are dismissed out of hand. The last point may be familiar to Prof. Bauer, who is no stranger to readers of these pages. He has long held a contrarian position on the causes of AIDS and I imagine that the rejection of his views can sting. Still, it's not clear what exactly has motivated Prof. Bauer's wide-ranging essay, unless it's just the lure of crusading against the imposed groupthink of mainstream science. That is fine and may well offer some good sparring as long as one prepares one's case well. Unfortunately, Prof. Bauer has not done so and his arguments against AGW don't stand up when confronted with the data and research. To make his case, Exhibit A is the booklet Climate Change: Evidence and Causes published by the London Royal Society in collaboration with the US National Academy of Sciences which he dissects for us in his essay. In a nutshell, he argues that since the science is patently wrong, disseminating a pamphlet affirming it amounts to proof of collaborative propagandizing. Along the way we learn that comparisons with previous documents, duplicitous choices of wording, and even the use of British spelling providesupporting evidence of the collusion. However, it's not necessary to debate these points. To undo Prof. Bauer's argument, it suffices to expose the errors in his claim that the science wrong. The rest of his propaganda argument falls after that.